An Examination of Gender Differences in Bullying among Justice-involved Adolescents. Issue 2 (1st February 2021) - Dembo, Richard; Krupa, Julie M.; Faber, Jessica; DiClemente, Ralph J.; Wareham, Jennifer; Schmeidler, James
ABSTRACT: Most studies of bullying rely on school-based samples of youth; however, a few studies of justice-involved populations suggest delinquent youth experience higher rates of bullying than youth in the general population. Little is known about gender differences in bullying among justice-involved youth. Using data from a Health Coach service project for justice-involve youth implemented at two intake facilities, 312 female and 857 male newly arrested youth were included in the current study. The current study sought to determine gender differences in prevalence rates of bullying involvement. Logistic regression was used to explore gender differences in how key covariates of demographic, risk factors, and traumatic experiences related to bullying. Rates of bullying experiences were higher for girls (35%) than boys (17%), and these rates were higher than rates reported in studies using general population or school-based samples. Analysis revealed differences in risk factors of bullying by gender. For both arrested girls and boys, depressive symptoms and sexual assault victimization increased the odds of bullying. Justice-involved youth are at greater risk of bullying and experience multiple problems. Holistic treatment and prevention strategies that recognize the co-occurrence of mental health symptoms, serious victimization, and substance abuse with bullying experiences are needed.